2018
DOI: 10.1083/jcb.201711083
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LAMP1-labeled nondegradative lysosomal and endocytic compartments in neurons

Abstract: Despite widespread distribution of LAMP1 and the heterogeneous nature of LAMP1-labeled compartments, LAMP1 is routinely used as a lysosomal marker, and LAMP1-positive organelles are often referred to as lysosomes. In this study, we use immunoelectron microscopy and confocal imaging to provide quantitative analysis of LAMP1 distribution in various autophagic and endolysosomal organelles in neurons. Our study demonstrates that a significant portion of LAMP1-labeled organelles do not contain detectable lysosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
205
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(227 citation statements)
references
References 61 publications
21
205
1
Order By: Relevance
“…Run length and instant velocity were not affected (Fig M and N). Overall, LAMP1‐labeled vesicles were slightly more mobile than LysoTracker‐stained organelles, which probably has to do with the broader spectrum of endolysosomal compartments labeled by LAMP1 (Cheng et al , ). Altogether, these data indicate a contribution of the dendritic F‐actin cytoskeleton in directing trafficking of lysosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Run length and instant velocity were not affected (Fig M and N). Overall, LAMP1‐labeled vesicles were slightly more mobile than LysoTracker‐stained organelles, which probably has to do with the broader spectrum of endolysosomal compartments labeled by LAMP1 (Cheng et al , ). Altogether, these data indicate a contribution of the dendritic F‐actin cytoskeleton in directing trafficking of lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Cheng and colleagues performed a rigorous characterization of LAMP1‐positive compartments in dendrites. They found that about half of the LAMP1‐labeled structures contained functional lysosomal proteases cathepsins B and D, markers for mature lysosomes (Cheng et al , ). It has also been shown that neuronal activity induces lysosomal exocytosis and release of cathepsins (Padamsey et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Since STX16 knockout resulted in reduced cellular content of LAMP1/2, which is in lysosomal and additional acidified endosomal compartments (Lippincott-Schwartz & Fambrough, 1987) (Cheng et al, 2018), we anticipated that the cells might have diminished content of acidified organelles. We used LysoTracker Red DND-99 (LTR) as a standard cell biological probe for acidification of intracellular compartments (Wubbolts et al, 1996).…”
Section: Stx16 Affects Mtor Regulationmentioning
confidence: 99%
“…Similarly, we found that LAMP1-eGFP vesicles became more mobile following actin depolymerization ( Figure 5H-K) and the directional net flux was no longer biased towards anterograde trafficking ( Figure 5L). Overall, LAMP1-labelled vesicles were slightly more mobile than LysoTracker stained organelles, which probably has to do with the broader spectrum of endolysosomal compartments labeled by LAMP1 (Cheng et al, 2018). Altogether, these data suggest a contribution of the dendritic F-actin cytoskeleton in directing trafficking of lysosomes.…”
Section: Dendritic F-actin Patches Are Spatially Segregated From Thementioning
confidence: 75%
“…To address the question if dendritic actin patches influence organelle trafficking, we chose to look at lysosomes as a representative vesicular organelle, because they show very active, processive trafficking along dendrites, and recently more and more studies are emerging that highlight their significance in neuronal function (Cheng et al, 2018;Goo et al, 2017;Padamsey et al, 2017). First, we used 3-color STED to visualize the spatial relationship between F-actin, MTs and lysosomes, using antibodies against the lysosomal marker protein LAMP1.…”
Section: Dendritic F-actin Patches Are Spatially Segregated From Thementioning
confidence: 99%